1994
DOI: 10.1111/j.1474-919x.1994.tb01100.x
|View full text |Cite
|
Sign up to set email alerts
|

Colonial breeding and nest predation in the Jackdaw Corvus monedula using old Black Woodpecker Dryocopus martius holes

Abstract: Jackdaws Corvus monedula breeding in old holes of the Black Woodpecker Dryocopus martius were studied during 6 years in central Sweden. Of 131 breeding attempts, only 56% were successful. Nest predation caused 74% of the breeding failures. The most common predator was probably the Pine Marten Mattes mattes, as fresh hair was found in 42% of the nests whose contents had been predated. Predation risk of nest contents was not related to the height above ground, but it was significantly reduced with increasing col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Studies have shown that, outside the breeding season, reducing the area of a high-quality patch significantly reduces the size of heterospecific foraging groups (Beauchamp 2008;Siffczyk et al 2003), which decreases the probability of an approaching predator being detected (Beauchamp 2008;Griesser 2009). During the reproductive season, breeding success may increase with the number of close neighbours including heterospecifics (Alatalo and Lundberg 1984;Berg et al 1992;Fuchs 1977;Haas 1985;Johnsson 1994;Patterson 1965;Wiklund and Andersson 1994), which, in turn, is higher in high-quality habitats. In some bird species, there is a strong association between egg and nestling survival in groups as opposed to nesting alone (Götmark and Andersson 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that, outside the breeding season, reducing the area of a high-quality patch significantly reduces the size of heterospecific foraging groups (Beauchamp 2008;Siffczyk et al 2003), which decreases the probability of an approaching predator being detected (Beauchamp 2008;Griesser 2009). During the reproductive season, breeding success may increase with the number of close neighbours including heterospecifics (Alatalo and Lundberg 1984;Berg et al 1992;Fuchs 1977;Haas 1985;Johnsson 1994;Patterson 1965;Wiklund and Andersson 1994), which, in turn, is higher in high-quality habitats. In some bird species, there is a strong association between egg and nestling survival in groups as opposed to nesting alone (Götmark and Andersson 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Based on these assumptions we can infer that favourable conditions for treenesting are indeed found only in hilly regions of NE Slovenia like Slovenske gorice and Goričko, where the majority of forest-nesting pairs was recorded. Here, open agricultural areas interspersed with small beechforest islands form mosaic-like countryside with a total forest area of c. 30% (Perko & Orožen Adamič 1999), corresponding to descriptions of habitat in different regions of Europe with prevailing tree-nesters (Johnsson 1994, Samwald 1996, Rudolph 2000.…”
Section: Discussionmentioning
confidence: 99%
“…Lorenz 1931, Röel 1978, Schwab et al 2008, Davidson et al 2014, Kubitza et al 2015. Also, many studies of breeding biology, nest site selection, breeding and foraging habitat characteristics and predation were carried out throughout Europe (Antikainen 1980, 1987, Johnsson 1994, Soler & Soler 1993, Biondo 1998, Salvati 2002a, Unger & Peter 2002, Arnold & Griffiths 2003. Jackdaw is unique within genus Corvus by nesting in cavities, either natural or manmade.…”
Section: Introductionmentioning
confidence: 99%
“…Nest predation is a major cause of nesting failure in birds (Ricklefs 1969, Martin 1993). Many bird species have tactics to avoid nest predation, such as selecting well‐protected nest sites (Martin and Roper 1988, Kelly 1993, Whittingham et al 2002), or by defending nests vigorously (Larsen 1991, Johnsson 1994). Among the traits that probably evolved under the pressure of nest predation is the nesting of ‘timid’ bird species close to ‘aggressive’ raptor species: the ‘timid’ bird reduces the rate of predation of its nests because of the raptor's defense of its own nearby nest (Wiklund 1982, Blanco and Tella 1997, Bogliani et al 1999, Quinn and Kokorev 2002, Quinn et al 2003).…”
mentioning
confidence: 99%